A Retrospective Cohort Single-Centre Study of Prophylactic Vs. Preemptive Valganciclovir Therapy in Cytomegalovirus-At-Risk Kidney Transplant Recipients in Malaysia - Mastuki, Mohd Fahmi; Masri, Siti Norbaya; Mohd Lila, Mohd Azmi; Camalxaman, Siti Nazrina; Idris, Salmah; Mohd Taib, Niazlin (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Valganciclovir is commonly used for prophylaxis or preemptive therapy to prevent post-transplant cytomegalovirus (CMV) infection and disease in kidney transplant recipients. However, there are a limited data on the outcome and the association between valganciclovir and clinical characteristics of kidney transplant recipients, particularly those who are CMV seronegative (R-) receiving a transplant from CMV seropositive donors (D+), as well as in populations with high CMV seroprevalence. MATERIALS AND METHODS: This retrospective, single-center cohort study collected clinical data from kidney transplantation recipients at a tertiary referral hospital from January 2020 to June 2022. The data on the recipients’ demographics, CMV risk categories, clinical characteristics, and types of valganciclovir therapy were obtained. Associations between clinical data, CMV risk categories, and therapies were determined. RESULTS: Among 110 kidney recipients, 9 were classified as high-risk and 101 as intermediate-risk. There were no significant differences found in the recipients’ demographics and underlying factors between the risk categories. CMV infection occurred significantly less in the prophylaxis group than in the preemptive group (22.2% vs. 59.4%, p=0.04). There were no significant differences in one-year graft outcomes or patient survival observed between prophylaxis and preemptive therapies. Leukopenia incidence was higher in patients receiving prophylaxis. The incidence of co[1]infection with CMV viremia was similar between high-risk and intermediate-risk recipients. A significant association was found between CMV risk categories and prophylactic therapy in relation to post-transplant complications, CMV viremia clearance duration, and peak titer. CONCLUSION: Valganciclovir was the preferred therapy to prevent CMV infection and disease in kidney transplant recipients, with prophylactic therapy showing particular benefit in high-risk groups without increasing complications.